Burmese Culture during the Colonial Period in the Years 1885-1931. The World of Burmese Values in Reaction to the Inclusion of Colonialism - Tobiasz Targosz (Ksiegarnia Akademicka Publishing, 2021)
The colonial period in Burma marked the start of slow changes which would eventually turn a traditional society into a modern one. The changes in Burmese culture which took place in the colonial period were an important aspect of this transformation. In the period of British rule, Burmese culture found itself in an ambivalent situation, on the one hand opposing foreign models and ideas and, on the other, adopting numerous foreign cultural elements which, if treated as cultural tools, allowed for the protection of autotelic indigenous Burmese values.